1970
DOI: 10.1099/00221287-63-3-311
|View full text |Cite
|
Sign up to set email alerts
|

The Endoplasmic Reticulum as the Site of Potassium Tellurite Reduction in Yeasts

Abstract: S U M M A R YPotassium tellurite (K,TeO,) reduction in the obligate aerobe Rhodotorula nzuciluginosa 49 and the facultative anaerobe Saccharomyces cerevisiae 1-434 occurs on localized areas of endoplasmic reticulum. The reduction product is granular and is found in close association with the membranes of specific parts of the endoplasmic reticulum. The site of reduction is the same whether R. mucilaginosa 49 is grown on a respiratory substrate (sodium malate) or a fermentable substrate (glucose).Increasing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Electron microscopy revealed that, as previously reported in budding yeasts (Corfield & Smith, 1970), the reduction product after growth in tellurite was deposited on membranes in localized areas of the cytoplasm (Fig. 3).…”
Section: Results a N D Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Electron microscopy revealed that, as previously reported in budding yeasts (Corfield & Smith, 1970), the reduction product after growth in tellurite was deposited on membranes in localized areas of the cytoplasm (Fig. 3).…”
Section: Results a N D Discussionsupporting
confidence: 82%
“…When the yeasts Saccharomyces cerevisiae and Rhodotorula inucilagitiosn are grown in the presence of K,TeO, the reduction product is deposited mainly on specialized areas of endoplasmic reticulum (Corfield & Smith, 1970). The present report concerns the effect of tellurite on the fission yeast Schizosaccharoiizyces ponzbe.…”
Section: Introductionmentioning
confidence: 91%
“…The respiratory-competent cells do not multiply in the presence of glycerol and tellurite, which indicates that respiration is completely inhibited (Corfield and Smith, 1970;Massardo et al, 2009). In this work, the choice of the respiratory-deficient mutants with different mitochondrial genotypes was stimulated by the recent reports on the effects of both mtDNA and mitochondrial membranes on the morphology and architecture of mitochondria, respectively (Xu et al, 2005;Harner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to reduce Te is not restricted to prokaryotes, but also eukaryotes, including fungi, yeasts, plants and animal tissues that may carry out various reactions leading to form black Te 0 precipitates (Barrnett and Palade, 1957;Nagai, 1965;Corfield and Smith, 1970;Smith, 1974;Gharieb and Gadd, 1998;Ollivier et al, 2008;Zannoni et al, 2008;Massardo et al, 2009). Tucker et al (1962) demonstrated by X-ray diffraction analysis that the black precipitate produced in bacterial cells grown in potassium tellurite medium consisted of metallic tellurium (Te 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is only a limited amount of evidence for reduction of Hi+ to HgO in fungi and yeasts in contrast to bacteria. Fungal reductions of metalloids include reduction of tellurite to elemental tellurium, whieh can appear as a black deposit and located on the endoplasmic reticulum (Corfteld and Smith, 1970) and the reduction of selenate or selenite to form amorphous elemental selenium (Konetzka, 1977).…”
Section: Metal Transformationsmentioning
confidence: 99%